2012
DOI: 10.1007/s00436-012-2852-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of IL-12 genetic adjuvant and alum non-genetic adjuvant on the efficiency of the cocktail DNA vaccine containing plasmids encoding SAG-1 and ROP-2 of Toxoplasma gondii

Abstract: Various methods are available for enhancing the potency of DNA vaccines, including employment of different forms of adjuvant. The current study was carried out to evaluate and compare the effects of genetic and non-genetic adjuvants on the immune response stimulated by DNA vaccine. Thus, two adjuvants, IL-12 (genetic adjuvant) and aluminum hydroxide (alum, non-genetic adjuvant), were used with cocktail DNA vaccine containing plasmids encoding complete rhoptry antigen 2 (ROP-2) and surface major antigen 1 (SAG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…In this investigation, our data demonstrated that both cell subtypes were significantly accumulated in response to immunization with TgDPA. This result corresponds with reports regarding immunological responses to T. gondii antigens [16, 68–72]. …”
Section: Discussionsupporting
confidence: 92%
“…In this investigation, our data demonstrated that both cell subtypes were significantly accumulated in response to immunization with TgDPA. This result corresponds with reports regarding immunological responses to T. gondii antigens [16, 68–72]. …”
Section: Discussionsupporting
confidence: 92%
“…It is probably related with over stimulations of immune responses, caused by IL‐12. Additionally, in some of previous studies which used IL‐12 as an adjuvant, reported a lower immunogenicity …”
Section: Discussionmentioning
confidence: 99%
“…Currently, candidate vaccines that have been testing in mice are in the focus of protective antigen selections from membrane-associated surface antigens, excreted-secreted dense granule proteins, rhoptry proteins and micronemal proteins [6][8]. Of interests, rhoptry proteins (ROPs) excreted by rhoptries of the apical secretory organelles are involved in parasitic invasion [9].…”
Section: Introductionmentioning
confidence: 99%